Efektivitas Aplikasi My Sawit Dalam Peningkatan Penjualan Pada Pusat Penelitian Kelapa Sawit Medan (Studi Kasus Jl.Brigjend Katamso No.51,Kp.Baru,Kec.Medan Maimun) - Eva Nur Setriani; Nur Fadhilah Ahmad Hasibuan (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to develop a web-based palm oil sales application at the Medan Palm Oil Research Center. The research method used is a qualitative method, a case study carried out by researchers at the Palm Oil Research Center on Jl. Brigjend Katamso No. 51, kp. Baru, Medan. Researchers collect data through observations and interviews, then the data is processed and analyzed so as to obtain temporary assumptions to draw conclusions from the results of these observations. The research results show that the website, called my palm oil, can increase the effectiveness of palm oil sales, especially in marketing palm oil sprouts, fertilizers, pesticides and other superior products. However, there are several shortcomings that need to be corrected, such as limited features and lack of cooperation with expeditions and users cannot access the application freely like general buying and selling applications. Overall, My Sawit is a useful tool for those in the agricultural industry who are looking for an easy way to shop for palm oil seeds and other related products. The development of the My Sawit application is expected to help increase the efficiency and effectiveness of sales of palm oil seeds and related products, as well as expanding PPKS market reach.